War, Memory, and the Politics of Humor : The Canard Enchaîné and World War I - Douglas, Allen, 1949- (Book collections on Project MUSE., 2002)
'War, Memory and the Politics of Humor' features carnage and cannibalism, gender and cross-dressing, drunks and heroes militarism and memory, all set against the background of World War I France.